Nano-adsorbents an effective candidate for removal of toxic pharmaceutical compounds from aqueous environment: A critical review on emerging trends. (June 2021) - Neha, Rajendran; Adithya, Srikanth; Jayaraman, Ramesh Sai; Gopinath, Kannappan Panchamoorthy; M, Pandimadevi; L, Praburaman; Arun, Jayaseelan
Abstract: Advancements in medical research has resulted in the modernization of healthcare facilities, subsequently leading to a higher level of production and usage of pharmaceuticals to sustain better quality of life. Pharmaceutical active compounds (PhACs) possess high genotoxicity and eco-toxicity thus presenting numerous side effects to living beings on long-term exposure. The fate and toxicity of PhACs were explored in detail, aiming to elucidate their occurrence and transmission in wastewater treatment systems (WWTPs). Adsorption of pharmaceutical compounds using Nano-adsorbents has gained momentum in recent years owing to their low-cost, high surface area and effectiveness. This review has been conducted in order to widen the utilization of Nano adsorbents in the adsorption of pharmaceutical compounds with a focus on the aqueous environment. The synthesis routes and properties of Nano-adsorbents for removal of PhACs were assessed in a comprehensive way. The recovery and reuse ability of nano-adsorbents also forms an integral part of its application in the removal of PhACs and has hence been delineated. Graphical abstract: Image 1 Highlights : Sources, Eco-toxicity and Geno-toxicity of pharmaceutical compounds. Government regulations pertaining to disposal of pharmaceutical compounds. Synthesis, regeneration and reuse ability of nano-adsorbents. Removal and adsorption of pharmaceutical active compounds using nano-adsorbents.